2003
DOI: 10.2190/309d-7hqx-d4j4-t6tr
|View full text |Cite
|
Sign up to set email alerts
|

Ptsd, Depression, and Health Status in Lebanese Civilians Exposed to a Church Explosion

Abstract: The results suggest that PTSD, depression, and health status deterioration in trauma victims may persist over time. Resources such as social support can help attenuate the symptoms of those at a higher risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
41
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 25 publications
5
41
1
1
Order By: Relevance
“…However, the difficulty in comparing studies of different populations exposed to armed-conflict has to be emphasized because of variability in factors such as level of trauma exposure; time elapsed between exposure and diagnosis, other methodological differences and cultural factors. This study revealed that, being a female rather than a male was a common significant predictor for PTSD in both groups, which is in consonant with the findings of other previous studies that reported same [4,8,10] . In support of this, it has been documented that women use dissociative defense mechanism more than men and also have more negative self-schemas and world-schemas than men following exposure to traumatic events.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, the difficulty in comparing studies of different populations exposed to armed-conflict has to be emphasized because of variability in factors such as level of trauma exposure; time elapsed between exposure and diagnosis, other methodological differences and cultural factors. This study revealed that, being a female rather than a male was a common significant predictor for PTSD in both groups, which is in consonant with the findings of other previous studies that reported same [4,8,10] . In support of this, it has been documented that women use dissociative defense mechanism more than men and also have more negative self-schemas and world-schemas than men following exposure to traumatic events.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, the prevalence of PTSD found among the post conflict survivors (55.5%) was similar to the 24.8-54% current prevalence found among post conflict survivors in Rwanda [11] , Lebanon [8] , Liberia [9] and Uganda [10] , but higher than the 10-15.1% found in Northern-Ireland [6] , and Turkey [7] , following exposure to mass violence in these countries. Similarly, the rate in the group not exposed to conflict was close to the 9.4% prevalence of current PTSD reported among the Israeli general population [5] .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Also, financial difficulties have already been identified in the literature as a stable risk factor for PTSD (Chou et al, 2007;Farhood & Noureddine, 2003;Galea, Tracy, Norris, & Coffey, 2008). In the student body, those who did not face financial difficulties were mainly in the lower levels of the disorder, while those who had to face important changes in their monthly income presented a higher prevalence of PTSD symptoms.…”
Section: Discussionmentioning
confidence: 92%